Domestic wheat demand in a deregulated environment: modeling the importance of quality characteristics - Edwards, Lawrence James (Department of Sociology, 2025)
The implementation of the Marketing of Agricultural Produ~ts Bill, 1996, and the tariffication of agricultural goods in accordance with the Marrakesh Agreement has significant implications for the domestic wheat industry. The new regulations challenge the ossified single-channel fixed price marketing structure of the past and expose domestic producers and processors to increased price volatility, a higher risk exposure and regional and international competition for a market share. The focus of the new marketing system is that of demand; a substantial shift from the producer orientated system of the past. A consequence is the ascendancy of quality as a determinant of wheat demand. Past models of deregulation and trade liberalisation have ignored the role wheat quality will play in influencing the competitiveness of producers in relation to both domestic and international producers. Thus, a demand orientated cost minimising non-linear programming model (Input Characteristic Model) is developed which evaluates the demand for different wheat sources as a function of their quality characteristic levels, characteristic variances and prices. The quality characteristic data for the different sources of wheat were obtained from quality analyses done by the Wheat Board. Through the use of the dual and the inclusion of international sources of wheat, a set of regional prices for domestic wheat is determined. Using these prices, the response in demand for wheat to a number of market scenarios such as regional production variations, regional price variations and quality characteristic variations, are simulated. The results of the simulations suggest that a tariff of 66% as proposed by the Wheat Forum in 1994 overprotects the industry and will lead to substantial increases in bread prices. Further, the Western Cape faces a quality constraint in terms of its ability to compete with international· and domestic wheat sources. Protection through tariffs is only a short term solution and a substitution towards higher quality wheat or other crops is necessary. Lastly, the importance placed on wheat quality data, a reliable grading system, accurate price, production and quality predictions and research into improving wheat cultivars suggests the need for continued involvement in the wheat industry by institutions such as the Wheat Board.